Korean Bongsan Talchum mask theatre: A window to the past and the pride of the present - Yuri G. Smertin (RUDN Journal of World History)
Masked folk theatre performances in medieval Korea were apparently the only socially acceptable form of artistic expression of common people. They expressed popular mindsets, aspirations, and desires in stereotyped images. The study of this cultural phenomenon can reveal much about Korean national character. The study aims to analyze the content of a Bongsan Talchum play and to reveal its deeper meanings through the prism of history and ethno-psychology. The study is based on a full text of a play published by Korean scholar Cho Okon. In Russian historiography, there are no academic works on the history of Bongsan Talchum theatre. The author relies on the works of Korean and Western researchers, who to a greater or lesser extent covered the history and current state of this type of mask theatre, as well as on his personal impressions obtained during his academic internship in South Korea. The research concludes that Bongsan Talchum in its criticism of negative aspects of social reality did not oppose established norms and existing orders, but satirized undesirable deviations from those. It was a short-term expression of an alternative value system and had a compensatory function. At present, Bongsan Talchum is becoming a cultural symbol of Korea both at home and abroad.